Irrigated Fodder Production for Sheep Fattening - International Livestock Research Institute (International Food Policy Research Institute, 2019)
Feed shortage and poor quality of available feeds are major constraints for livestock production in the highlands of Ethiopia. A trial was conducted to assess if producing irrigated oat-vetch fodder during the dry period could adequately supplement the diet of fattening sheep and generate additional income for smallholders. For this purpose, a group of interested farmers from two districts (Lemo and Angacha) in southern Ethiopia were sensitized and trained to produce oat-vetch fodder with irrigation using water from shallow wells as well as manual pumps. A total of 14 farmers participated in the trail with each farmer fattening 5 sheep for about 70 days by supplementing approximately 200 g dry matter oat-vetch fodder per day. This dataset contains the body weight development of the sheep and the nutritional composition of local feed resources and the supplemental irrigated fodder used for the experiment.